A comparative study of effectiveness of local injection of autologous platelet rich plasma and injection corticosteroid solution in treatment of plantar fasciitis - Prakash Puri, Vithal; Kumar Gaur, Anil (International Journal of Research in Orthopaedics, 2019)
Background: The heel pain is the most common problem worldwide and it was associated with plantar fasciitis (PF). The condition of treatment is very complex. Platelet-rich plasma (PRP) and injection of corticosteroids is the treatment of PF. This study was designed to access the effect of local PRP and local corticosteroid injection in PF patients. Methods: Sixty patients (between 29 to 60 years of age) with chronic PF were randomized prospectively in single tertiary care center in India. The study conducted from December 2013 to December 2015. All the patients were enrolled according to inclusion criteria and divided into two groups randomized. In group A (n=30) received PRP and group B (n=30) received corticosteroids injections. Visual analog scales (VAS) were filled by all the included patients. The follow-up scheduled at one and six months after complete enrolment of patients. Results: Between both the groups the significantly different observed at one and six months follow-up from the baseline. At one month follow-up significantly improvement in mean VAS score were observed in group B (p<0.001). At six months follow-up significantly improvement in mean VAS score were observed in group A (p<0.001). Conclusions: The present study concluded from the significance difference between both the groups proved promising form of treatment in chronic PF patients. Both the treatment was safe and effective in relieving pain improving function at different time period.